Investing in Socially Responsible Mutual Funds. (11th February 2021) - Geczy, Christopher C; Stambaugh, Robert F; Levin, David
Abstract: We construct optimal portfolios of mutual funds whose objectives include socially responsible investment (SRI). Comparing portfolios of these funds to those constructed from the broader fund universe reveals the cost of imposing the SRI constraint on investors seeking the highest Sharpe ratio. This SRI cost crucially depends on the investor's views about asset pricing models and stock-picking skill by fund managers. To an investor who strongly believes in the CAPM and rules out managerial skill, that is, a market index investor, the cost of the SRI constraint is typically just a few basis points per month, measured in certainty-equivalent loss. To an investor who still disallows skill but instead believes to some degree in pricing models that associate higher returns with exposures to size, value, and momentum factors, the SRI constraint is much costlier, typically by at least 30 basis points per month. The SRI constraint imposes large costs on investors whose beliefs allow a substantial amount of fund-manager skill, that is, investors who heavily rely on individual funds' track records to predict future performance. ( JEL G11, G12, C11) In 2005, when we released what ultimately proved to be the final version of this study, socially responsible investment (SRI) had already become a major presence on the investment landscape. In the years since, this approach, now often called "sustainable" investment, has grown even more rapidly and often encompasses a broad set of "ESG" (environmental, social, and governance) criteria. As evidence of the rapid growth, Morningstar (2020) notes, "one need look no further than the nearly fourfold increase in assets that flowed into sustainable funds in the United States in 2019." Sustainable investing has also received increased attention in the academic literature, in subsequent studies too numerous to list. Some of the studies are especially related to ours in that they also examine mutual funds. In our study, mutual funds constitute an asset universe faced by an investor imposing an SRI/ESG constraint. A number of the subsequent studies use mutual funds to address other dimensions of sustainable investing. For example, Bollen (2007), Benson and Humphrey (2008), Renneboog, Ter Horst, and Zhang (2011), Bialkowski and Starks (2016) and Hartzmark and Sussman (2019) investigate determinants of mutual fund flows into sustainable funds versus other funds. Riedl and Smeets (2017) use survey and experimental data to explore investors' preferences for sustainable funds. Madhavan et al. (2020) examine sustainable active equity mutual funds, relating factor loadings and residual returns to ESG characteristics. While we focus on mutual funds, our study also intends that the basic aspects of the SRI setting extend to other institutional investors. That intent is supported, for example, by the recent evidence of Bolton and Kacperczyk (forthcoming, 2020 ) providing broader perspectives on the SRI portfolio tilts of various types of institutional investors.One conclusion of our study is that an SRI/ESG constraint is especially binding for investors wishing to tilt toward value or small-cap funds. It seems reasonable to infer that such is still the case, though we have not updated our formal analysis. For example, Morningstar (2020) identifies, as of 2019, 99 sustainable U.S. equity funds categorized within its 3 × 3 style box that sorts along the dimensions of value/blend/growth and small/mid-cap/large. Of those 99 funds, only 8 are classified as value, versus 24 as growth and 67 as blend. Only 7 of the 99 are small-cap funds, versus 79 large-cap and 13 mid-cap. More generally, our 2005 study is early in noting meaningful differences in factor loadings between sustainable versus other funds, in both three- and four-factor models.An SRI/ESG constraint is also especially binding for investors who see much information in individual funds' historical alphas. The basic reason we discuss in our study is seemingly still at work. That is, despite the rapid growth noted earlier, the number of sustainable funds is still well less than those in the total fund universe, so many of the highest track records appear among funds outside that subset. Not mentioned in our original study is that the case of an investor who sees much information in historical alpha confronts the argument of Berk and Green (2004) : if fund flows rationally respond to historical alpha, an investor will not view historical alpha as being informative about future alpha. That argument relies on investors correctly assessing the degree of fund-level decreasing returns to scale. One might view an investor who sees historical alpha as informative about future alpha as also having beliefs that favor a lower degree of decreasing returns to scale, as compared to other investors. Moreover, the equilibrating effects of fund flows might interact with the nonpecuniary utility that SRI-conscious investors derive from their fund choices, as suggested by the evidence of Bollen (2007) that flows respond to returns differently for SRI funds versus conventional funds. In any event, when prior beliefs admit substantial information from historical alphas, Busse and Irvine (2006) find that Bayesian predictive alphas computed as in Pástor and Stambaugh (2002a, 2002b ), as are the alphas in our study, do predict future performance.While not one we address, a question often asked is whether sustainable investments perform better or worse than other investments. A number of studies do pursue this question, obtaining a range of findings that include both higher and lower performance for sustainable investments. Pástor, Stambaugh, and Taylor (forthcoming) discuss the challenge in interpreting such findings' implications about expected future performance. A wedge between ex ante and ex post performance of sustainable investments arises during any period that witnesses unanticipated shifts in either customers' demands for sustainable products or investors' demands for sustainable holdings. 1 As those authors note, sorting out such effects is an important challenge for future research. Our study conducts its analysis under a variety of asset pricing models and prior beliefs. In each case, an investor conditions on funds' past returns and thus takes account of any historical performance differences between the sustainable funds and other funds in our sample. We do not, however, include models in which expected asset returns depend on sustainability. In this respect, our study does not attempt to provide direct evidence about a potential relation between sustainability and expected investment performance.We are grateful to the Review of Asset Pricing Studies for the opportunity to publish our original study, which follows below with only the references updated to reflect subsequent publications. The study's abstract is also unchanged from its original version.